Heat Treatment, Microstructure and Corrosion Relationship on 316L SS Produced by AM. Issue 6 (13th April 2023) - Özer, Gökhan
ABSTRACT: In this study, 316L stainless steel (SS) samples produced with standard parameters using the Additive Manufacturing method were heat treated with different parameters, and the effects of heat treatment on the microstructure, phase changes, hardness, porosity, and corrosion of the material were examined in detail. The results showed that the as-built microstructure of 316L stainless steel material produced by Additive Manufacturing deteriorated as the heat treatment temperature increased and the hardness decreased. The corrosion resistance of the material increased. The best corrosion resistance was obtained from heat treatment at 1150°C for 2 h.